2017
DOI: 10.1080/01443615.2017.1283304
|View full text |Cite
|
Sign up to set email alerts
|

Date fruit consumption at term: Effect on length of gestation, labour and delivery

Abstract: Labour induction and augmentation with Prostaglandin and Oxytocin are well established as standard practice worldwide. They are safe when used judiciously, but may be associated with maternal and neonatal morbidities. Other safer alternatives have been studied including dates consumption during late pregnancy with various outcomes. The aim of this randomised controlled trial was to investigate the effect of date fruit consumption during late pregnancy on the onset of labour and need for induction or augmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
4
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 10 publications
1
55
4
8
Order By: Relevance
“…We gathered 1531 studies from databases and other hand search sources. Eight of 1531 studies (Eight fulltext papers under six trials) had eligibility criteria and were included in qualitative and quantitative analysis [33][34][35][36][37][38][39][40]. Three of them had the same ethic code (910732) (approval code of research ethics committee) and were different reports of one trial [33][34][35].…”
Section: General Characteristicsmentioning
confidence: 99%
“…We gathered 1531 studies from databases and other hand search sources. Eight of 1531 studies (Eight fulltext papers under six trials) had eligibility criteria and were included in qualitative and quantitative analysis [33][34][35][36][37][38][39][40]. Three of them had the same ethic code (910732) (approval code of research ethics committee) and were different reports of one trial [33][34][35].…”
Section: General Characteristicsmentioning
confidence: 99%
“…It has a high nutritional value and is rich in carbohydrates such as glucose and fructose (70%), protein, B vitamins, minerals, antioxidants, and tannins (21). Some studies investigated the many medicinal applications of date palm, including antiinflammatory and analgesic effects (22,23), labor induction (23)(24)(25)(26), and sedation (27).…”
Section: Introductionmentioning
confidence: 99%
“…We gathered 1531 studies from databases and other hand search sources. Nine of 1531 studies (Nine full-text papers under six trials) had eligibility criteria and were included in qualitative and quantitative analysis [33][34][35][36][37][38][39][40][41]. Three of them had the same ethic code (910732) (approval code of research ethics committee) and were different reports of one trial [33][34][35].…”
Section: General Characteristicsmentioning
confidence: 99%
“…The flowchart of searching and inclusion process of studies is shown in Figure 1(According to PRISMA statement). Five of included studies had used the date palm fruit [33,36,[39][40][41], and one study had used date fruit honey [38]. Descriptions and characteristics of the reviewed studies are shown in Table 1 sizes of these studies were 89 to 210 participants.…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation